2019
DOI: 10.1080/15284336.2019.1603433
|View full text |Cite
|
Sign up to set email alerts
|

Retention in clinical trials after prison release: results from a clinical trial with incarcerated men with HIV and opioid dependence in Malaysia

Abstract: Background: Study retention is a major challenge in HIV clinical trials conducted with persons recruited from correctional facilities.Objective: To examine study retention in a trial of within-prison methadone initiation and a behavioral intervention among incarcerated men living with HIV and opioid dependence in Malaysia. Methods:In this 2×2 factorial trial, 296 incarcerated men with HIV and opioid dependence were allocated to 1) an HIV risk reduction intervention, the Holistic Health Recovery Program for Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…It should be noted that methadone could have positively impacted other health and social outcomes in our sample including potentially by reducing injection drug use, but this was not the focus of this analysis. Implementation challenges as well as barriers and facilitators to postrelease retention in this trial have been previously reported [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that methadone could have positively impacted other health and social outcomes in our sample including potentially by reducing injection drug use, but this was not the focus of this analysis. Implementation challenges as well as barriers and facilitators to postrelease retention in this trial have been previously reported [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of the trial was sexual and injection-related risk behaviors during the first year postrelease [ 44 , 46 ]. In this paper, we present a secondary analysis of post-release mortality that was developed to more closely examine high rates of study attrition amidst high numbers of participant deaths.…”
Section: Methodsmentioning
confidence: 99%
“…Multivariable Cox regression incorporated time-to-event covariates such as methadone dosage (low, medium, high), previous experience of OAT, type of site, HIV status, and region. Since people released from prison are at increased risk of treatment discontinuation ( Bachireddy et al, 2022 ; Chandra et al, 2019 ), the estimates were controlled for the additional variable reflecting loss-to-follow-up after release. Hazard ratios were adjusted for the year of enrollment to minimize temporal change biases in treatment, political and secular trends.…”
Section: Methodsmentioning
confidence: 99%
“…The primary outcome of the trial was sexual and injection-related risk behaviors during the rst year postrelease [45,47]. In this paper, we present a secondary analysis of post-release mortality that was developed to more closely examine high rates of study attrition amidst high numbers of participant deaths.…”
Section: Methodsmentioning
confidence: 99%